2019
DOI: 10.3897/neotropical.14.e37919
|View full text |Cite
|
Sign up to set email alerts
|

Malformation in three anuran species from a preserved remnant of Atlantic Forest in southeastern Brazil

Abstract: Records of malformation in amphibians have significantly increased on a global scale. The main causes of malformations are linked to environmental contaminants, and records in preserved environments are uncommon. We reported malformations in three anuran species belonging to three families: Crossodactylustimbuhy (Hylodidae), Proceratophrysschirchi (Odontophrynidae) and Thoropamiliaris (Cycloramphidae). All records were found within the Reserva Biológica Augusto Ruschi, a well-preserved protected remnant of Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Although there are records in the northern hemisphere of malformations in amphibians caused by parasites or by the interaction of parasites with pesticides (Haas et al 2017), the parasite that causes such anomalies (Ribeiroia ondatrae) is restricted to the northern hemisphere. This suggests that the malformations we observed were caused by the herbicides that were applied, as has been observed in various other studies of amphibian malformations (e.g., Ouellet et al 1997;Lannoo 2008;Egea-Serrano et al 2012;Wagner et al 2013;Sparling et al 2015;Koleska and Jablonski 2016;Mônico et al 2019). Amphibians have high philopatry and low vagility (Wells 2007), making it possible to map the impact of herbicides on the landscape through the occurrence of individuals with malformations and the absence of species that were previously abundant.…”
supporting
confidence: 78%
“…Although there are records in the northern hemisphere of malformations in amphibians caused by parasites or by the interaction of parasites with pesticides (Haas et al 2017), the parasite that causes such anomalies (Ribeiroia ondatrae) is restricted to the northern hemisphere. This suggests that the malformations we observed were caused by the herbicides that were applied, as has been observed in various other studies of amphibian malformations (e.g., Ouellet et al 1997;Lannoo 2008;Egea-Serrano et al 2012;Wagner et al 2013;Sparling et al 2015;Koleska and Jablonski 2016;Mônico et al 2019). Amphibians have high philopatry and low vagility (Wells 2007), making it possible to map the impact of herbicides on the landscape through the occurrence of individuals with malformations and the absence of species that were previously abundant.…”
supporting
confidence: 78%
“…On 2003; Schoff et al 2003;Lunde and Johnson 2012;Henle et al 2017b;Monico et al 2019). Also, Ribeiroia ondatrae, a trematode parasite, is known to trigger limb malformations in anurans (Rajakaruna et al 2008;Szuroczki et al 2012).…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Smentioning
confidence: 99%
“…Various reports revealed that exposure to water contaminated with pollutants, pesticides, herbicides, retinoids and retinoid mimics, steroid-mimicking contaminants, petrochemicals, and metals, along with microbial diseases, parasitic infections, ultraviolet radiation, and global warming are principal causes of abnormalities in anurans (see Hall and Henry 1992;Chambon 1993;Kirk 1998;Marco et al 2002;Blaustein and Johnson 2003;Degitz et al 2003;Ankley et al 2002;Johnson et al 2001;Schoff et al 2003;Lunde and Johnson 2012;Henle et al 2017b;Monico et al 2019). The cause of this abnormality in this particular species and the extent of malformations among amphibians in the Hmuifang Community Reserve Forest are still unknown.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%